Direct numerical simulation of flame/spontaneous ignition interaction fueled with hydrogen under SACI engine conditions. (9th February 2017) - Zhang, F.; Yu, R.; Bai, X.S.; Yao, M.; Peng, Z.
Abstract: In spark assisted homogeneous charge compression ignition (SACI) engines a premixed flame is first established; the propagating flame results in compression heating of the end gas and finally auto-ignition of the gas. Two dimensional direct numerical simulation (2D DNS) and one dimensional (1D) detailed simulations of flame/spontaneous ignition interaction in a lean hydrogen/air mixture under a constant volume enclosure relevant to SACI engine conditions are performed using detailed chemistry and detailed transport properties. In a 2D outward propagating spherical flame, thermal-diffusive instability is observed and once auto-ignition starts a low temperature region in the preheat zone of the flame is formed. Subsequently, the ignition in the preheat zone is suppressed. Then 1D flame/ignition interactions in H2 /air, syngas/air and methane/air mixtures are studied using detailed numerical simulations. The results reveal that due to preferential diffusion of hydrogen, heat and mass transfer in the preheat zone inhibits the ignition process, yielding a slower reaction rate hence an even lower temperature in the region. It is shown further that the low temperature region is not affected by the domain size and one step chemistry but it will disappear at very low initial temperature conditions. This is due to the absence of auto-ignition under low temperature conditions. Highlights: Thermal-diffusive instability is observed in a 2D outward propagating flame. For a lean H2 /air mixture heat and mass transfer in the preheat zone inhibits ignition. Flame/ignition interactions are examined by elementary reaction path analysis. Detailed chemistry and a single step mechanism is used for comparison.